2001
DOI: 10.1111/j.1553-2712.2001.tb00541.x
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy of Esmolol versus Lidocaine to Attenuate the Hemodynamic Response to Intubation in Isolated Head Trauma Patients

Abstract: Abstract. Objective: To assess the effect of esmolol vs lidocaine to attenuate the detrimental rise in heart rate and blood pressure during intubation of patients with isolated head trauma. Methods: This was a prospective, double-blind, randomized study, performed at an urban, county teaching emergency department. Participants were 30 patients with isolated head trauma. Each underwent a standardized intubation protocol including esmolol or lidocaine, both at 2 mg/ kg. Results: Esmolol was used in 16 patients a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0
2

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 42 publications
2
6
0
2
Order By: Relevance
“…Moreover, another study by Ali et al in 2010 revealed that pre-treatment with xylocard improves intra- and post-operative hemodynamic stability during laparoscopic surgery without prolonging recovery (26). Our study was in line with some previous studies such as Shin et al that compared the effects of lidocaine, fentanyl, Nicardipine and Esmolol, on the hemodynamic response during intubation and that study revealed that all of these agents are effective in producing hemodynamic stability (27). Moreover, a study by Levitt et al found that Esmolol and lidocaine have similar efficacies to attenuate moderate hemodynamic responses to intubation in patients with isolated head trauma (28).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Moreover, another study by Ali et al in 2010 revealed that pre-treatment with xylocard improves intra- and post-operative hemodynamic stability during laparoscopic surgery without prolonging recovery (26). Our study was in line with some previous studies such as Shin et al that compared the effects of lidocaine, fentanyl, Nicardipine and Esmolol, on the hemodynamic response during intubation and that study revealed that all of these agents are effective in producing hemodynamic stability (27). Moreover, a study by Levitt et al found that Esmolol and lidocaine have similar efficacies to attenuate moderate hemodynamic responses to intubation in patients with isolated head trauma (28).…”
Section: Discussionsupporting
confidence: 93%
“…Our study was in line with some previous studies such as Shin et al that compared the effects of lidocaine, fentanyl, Nicardipine and Esmolol, on the hemodynamic response during intubation and that study revealed that all of these agents are effective in producing hemodynamic stability (27). Moreover, a study by Levitt et al found that Esmolol and lidocaine have similar efficacies to attenuate moderate hemodynamic responses to intubation in patients with isolated head trauma (28). Additionally, Malde and Sarode in a 2007 study compared lignocaine and fentanyl efficacy on hemodynamic stability and revealed that lignocaine and fentanyl both attenuated the rise in heart rate; however, fentanyl produced better results.…”
Section: Discussionsupporting
confidence: 93%
“…Lidocaine, a class 1B antiarrhythmic drug, has been used to diminish the hypertensive response, to reduce airway reactivity, to prevent intracranial hypertension, and to decrease the incidence of dysrrhythmias during intubation. 49 -51 Demonstrated effectiveness for these end points, however, has varied among reports, 50,52,53 and no evidence has clearly established that lidocaine improves outcomes in terms of a lower incidence of myocardial infarction or stroke. North American physicians use lidocaine more commonly as a preinduction agent for patients who are at risk of elevated intracranial pressure compared with physicians in Europe.…”
Section: Preinduction Drugsmentioning
confidence: 99%
“…27 According to Levitt et al Esmolol and lidocaine have similar efficacies to attenuate moderate hemodynamic responses to intubation in patients with isolated head trauma. 28 Additionally, Malde and Sarode in a 2007 study compared lignocaine and fentanyl efficacy on hemodynamic stability and revealed that lignocaine and fentanyl both attenuated the rise in heart rate, however, fentanyl produced better results. Lignocaine attenuated the rise in blood pressure with intubation while fentanyl inhibits it totally.…”
Section: Discussionmentioning
confidence: 99%